2013
DOI: 10.1007/s11743-013-1465-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surfactant Hydrophilicity on the Oil Solubilization and Rheological Behavior of a Nonionic Hexagonal Phase

Abstract: The effects of surfactant hydrophilicity on the phase behavior and rheology of a hexagonal phase (H 1 ) and related O/H 1 emulsions in a water/C 12 EO n /isohexadecane system (n = 7, 9) have been investigated. In this phase behavior study, a variety of surfactant aggregates (micellar, W m ; hexagonal, H 1 ; bicontinuous cubic, V 1 ; lamellar, L a ; inverse micellar, O m ) have been observed in water-C 12 EO n binary systems. The oil solubility of different surfactant aggregates was strongly affected by the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Surfactants are broadly shown to self-assemble into (a) discrete entities such as spheres, prolate ellipsoids, cylinders [11][12][13] or (b) continuous geometries wherein they are connected through macroscopic distances into hexagonal (1D), 14,15 lamellar (2D) [16][17][18] or bicontinuous/sponge phase (3D). [19][20][21] These three dimensional structures, also referred to as liquid crystalline structures, provide high viscosity and uidity to surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants are broadly shown to self-assemble into (a) discrete entities such as spheres, prolate ellipsoids, cylinders [11][12][13] or (b) continuous geometries wherein they are connected through macroscopic distances into hexagonal (1D), 14,15 lamellar (2D) [16][17][18] or bicontinuous/sponge phase (3D). [19][20][21] These three dimensional structures, also referred to as liquid crystalline structures, provide high viscosity and uidity to surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…However, Jafvert et al [30] reported that, for a nonpolar organic compound, an increased EON of a nonionic surfactant with the same C-chain length decreases the solubilization of hexachlorobenzene. Alam et al [40] reported a similar result, namely, that a reduction in oil solubility occurs with an increased EON of nonionic surfactants.…”
Section: Solubilization Of Pe In Nonionic Surfactantsmentioning
confidence: 99%
“…1c. Recently, Alam et al 52 also described the important role of surfactant hydrophilicity in the formation and rheology of LC-based emulsions; long-chain surfactants are especially more suitable for the formation of LC-based emulsions than short-chain surfactants. The formation of LC-based emulsions is not spontaneous, and several parameters must be considered during their preparation.…”
Section: Formation and Stability Of Lc-based Emulsionsmentioning
confidence: 99%